2020
DOI: 10.1049/iet-epa.2020.0182
|View full text |Cite
|
Sign up to set email alerts
|

Improved hotspot monitoring method for thermal management system of automotive traction motor

Abstract: Hotspots in traction motors of electric vehicles are normally considered to locate in end windings due to the loose packaging and no access to iron cores for heat dissipation. To ensure safety, end winding temperatures are typically monitored by thermocouples in thermal management systems for real‐time cooling control. However, the authors’ study finds that slot winding temperatures will exceed end winding temperatures under high‐speed operations due to the much higher additional loss caused by the alternating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In contrast, inverse modelling techniques based on temperature measurements have also been used extensively for estimating core losses, as demonstrated in studies by [16][17][18][19][20], as well as for fault monitoring, as shown in [21,22]. However, the accuracy of the measured temperature plays a crucial role in determining the accuracy of the solution to an inverse problem.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, inverse modelling techniques based on temperature measurements have also been used extensively for estimating core losses, as demonstrated in studies by [16][17][18][19][20], as well as for fault monitoring, as shown in [21,22]. However, the accuracy of the measured temperature plays a crucial role in determining the accuracy of the solution to an inverse problem.…”
Section: Introductionmentioning
confidence: 99%